2017
DOI: 10.1371/journal.pone.0176066
|View full text |Cite
|
Sign up to set email alerts
|

The role of climate and environmental variables in structuring bird assemblages in the Seasonally Dry Tropical Forests (SDTFs)

Abstract: Understanding the processes that influence species diversity is still a challenge in ecological studies. However, there are two main theories to discuss this topic, the niche theory and the neutral theory. Our objective was to understand the importance of environmental and spatial processes in structuring bird communities within the hydrological seasons in dry forest areas in northeastern Brazil. The study was conducted in two National Parks, the Serra da Capivara and Serra das Confusões National Parks, where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…The vertical bars are standard errors northeastern Brazil, highlighting the importance of landscape heterogeneity as a mechanism shaping bird communities in the Caatinga (Santos 2004;Araujo et al 2012;Gonçalves et al 2017). Landscape heterogeneity is one of the main sources of variation in bird diversity (Heezik and Seddon 1999;Gillespie and Walter 2001;Smith 2015) and its influence is not limited to arid and semiarid environments, or extreme climatic events (Wiens 1989). Despite the limited number of habitat replicates surveyed in the present study, it is possible that the differences in species richness between plots resulted, at least partly, from the drought conditions that dominated the study period, in particular, in 2012.…”
Section: Discussionmentioning
confidence: 87%
“…The vertical bars are standard errors northeastern Brazil, highlighting the importance of landscape heterogeneity as a mechanism shaping bird communities in the Caatinga (Santos 2004;Araujo et al 2012;Gonçalves et al 2017). Landscape heterogeneity is one of the main sources of variation in bird diversity (Heezik and Seddon 1999;Gillespie and Walter 2001;Smith 2015) and its influence is not limited to arid and semiarid environments, or extreme climatic events (Wiens 1989). Despite the limited number of habitat replicates surveyed in the present study, it is possible that the differences in species richness between plots resulted, at least partly, from the drought conditions that dominated the study period, in particular, in 2012.…”
Section: Discussionmentioning
confidence: 87%
“…This may be one of the reasons why the suitability area of P. fuscipes is significantly reduced in future predictions [ 39 , 40 ]. Humidity, solar radiation, and air temperature affect the metabolic rates of animals and plants in tropical forests [ 41 ]. Previous studies have also shown that P. fuscipes prefers to overwinter in crop fields with dense vegetation cover that is relatively sheltered from the wind and cold.…”
Section: Discussionmentioning
confidence: 99%
“…2016; Gonçalves et al . 2017; Bhakti et al . 2018) in which either environmental gradients, habitat structure, or both, were important drivers of the composition of the local bird metacommunity and supported a process of species sorting (Leibold et al .…”
Section: Discussionmentioning
confidence: 99%